Perancangan Prototype Aplikasi Rekam Medis Di Laboratorium Komputer Universitas Awal Bros - Desfa Anisa; Widya Putri (BULLET : Jurnal Multidisiplin Ilmu, 2022)
−Computer technology is no longer something foreign to society, especially for those who are directly involved in the computer world. With computer technology, data processing is much faster and easier and produces more accurate data compared to manual systems. The medical record application is an application that can manage patient data, in the application it contains the patient's identity, examination results, payments and other services that have been provided to patients. Practicum at the Computer Laboratory of the DIII Medical Record and Health Information Study Program at Awal Bros University is carried out every semester from semester I to semester V. To support student practicum activities, we need a medical record application that can be used by students in the Computer Laboratory. In the Computer Laboratory of the DIII Medical Record and Health Information Study Program, there are already several applications installed on each computer. However, it is still not enough to support activities during practicum. For this reason, it is necessary to add applications to each computer, so that students can better understand the use of medical record applications during the practicum. The purpose of this study was to design a medical record application in the Computer Laboratory of the Medical Record and Health Information Study Program at Awal Bros University. The method used in this research is the prototype method and the system is designed using the figma application.